Reflections on Method and Theory in Microhistory, Ethnohistory and Colonial Andean History - Arana Bustamante, Luis (2011)
I attempt here a revision about some methodological problems and research strategies with reference to some of my recent work (2010, 2009a y 2009b, 2008) in intertwined fields of ethnohistory, social history and microhistory. The general chosen procedure to facing challenging and complex documentation, was to use simultaneously various methodologies provided by modern historiography and anthropology. So, we use for example the so-called thick description (Geertz) and the ethnography of history (Sahlins) —with few o almost no use in Andean studies tradition— along with the more «normal» hermeneutic documental procedures and also the indiciary deduction of the microhistory of C. Ginzburg. The main proposal is that adequately tempered combination of these methodologies will permite us to improve the comprehensive analysis of arduous analytical problems posed by the so called indigenous colonial transformation in both spheres of historical practices and the transformation of culture and indigenous world of representations.